Perfil clínico-epidemiológico dos suspeitos e infectados pelo coronavírus 2019 na faixa etária pediátrica - Ribeiro, Andressa Pereira (2023)
Objective: The objective of this study was to evaluate the clinical and epidemiological aspects of hospitalized children with suspected or confirmed infection by the coronavirus in the age range of zero to 12 years. Method: A descriptive and cross-sectional study was conducted using a quantitative design. The study was conducted in two stages: the first involved interviews with the children's caregivers, through the application of a semi-structured questionnaire from January 2021 to August 2022. The second stage involved the review of 165 medical records of hospitalized patients between January 2021 and December 2022. The study included children with suspected or confirmed coronavirus infection who were admitted to the Hospital de Clínicas of the Federal University of Uberlândia (HC-UFU) in the age range of zero to 12 years. Results: Data analysis revealed differences in gender distribution between the years 2021 and 2022. In 2021, the majority of participants were female, representing 56.7% of the total, while in 2022, males accounted for 55.0% of the participants. Both years showed a predominance of children in the preschool and school-age groups, and the majority of children were of Caucasian race. The most common symptoms reported by caregivers were fever, cough, runny nose, and respiratory discomfort. The percentage of positive results for COVID-19 was higher in 2021 (86.7%) compared to 2022 (29.0%). Regarding the use of oxygen therapy during hospitalization, there was a reduction in the need for this treatment in 2022. Conclusion: The results of this study contribute to the understanding of the clinical and epidemiological characteristics of COVID-19 in children. The identification of the main symptoms and the understanding of the epidemiological factors related to COVID-19 in children are essential for the proper management of these cases and the implementation of effective prevention and control strategies.